Effectiveness of Marine Wildlife Rescue and Rehabilitation Centers in Chile in relation to strandings of sea turtles, penguins, sea lions, and sea otters - Allende-Marín, Nareth; García-Cegarra, Ana M. (Revista de Biología Marina y Oceanografía, 2022)
Marine Wildlife Rescue and Rehabilitation Centers (MWRRCs) are crucial for the rehabilitation of endangered marine species, such as penguins, sea turtles, sea lions, and/or sea otters. In Chile, rescue of marine fauna is coordinated by the National Fisheries and Aquaculture Service (SERNAPESCA). This organization is responsible for assisting stranded animals and transporting them to 6 of the 13 MWRRCs that exist throughout the 6,435 km coastline of the country. Stranding events were analyzed for two species of pinnipeds (Otaria flavescens and Arctocephalus australis), two species of penguins (Spheniscus humboldti and Spheniscus magellanicus), two species of chelonians (Chelonia mydas and Lepidochelys olivacea), and one species of sea otter (Lontra felina) found stranded at the coast of Chile during 2009-2019 period. Success in post-rehabilitation release of individuals was also examined. A total of 2,818 stranding events were recorded with a total of 3,198 stranded animals, corresponding to O. flavescens (52.9%), S. humboldti (20.4%), S. magellanicus (17.9%) and L. olivacea (4.3%). Of the 3,198 stranded animals, 721 specimens were referred to MWRRC, and only 136 were released post-rehabilitation. This shows an18.8% success rate in the release of marine fauna species post-rehabilitated in rescue centers after their stranding. It is necessary to improve coordination between SERNAPESCA and MWRRCs in Chile to improve the release rate and to increase the number of MWRRCs to recover endangered marine species that strand along the country’s coast.